0346 Differentiation of Naturalistic Sleep in Chronic Insomnia vs. Healthy Controls Using a Non-Contact Measurement Device. (25th May 2022) - Hansen, Devon; Finlay, Myles; Peterson, Mary; Gottlieb, Elie; Raymann, Roy; Buchwald, Dedra; Van Dongen, Hans; Watson, Nathaniel
Abstract: Introduction: Individuals with insomnia report poor sleep quality and non-restorative sleep, and often exhibit irregular sleep patterns over time. First night effects and logistical challenges make it difficult to accurately measure these sleep characteristics in the laboratory. Also, sensitivity to sleep disruption from obtrusive devices confounds sleep measurements in people with insomnia in their naturalistic setting. Non-contact devices (NCDs) may address these issues and enable ecologically valid, longitudinal and unobtrusive characterization of sleep in individuals with insomnia. We present results from a NCD, previously validated against polysomnography, – SleepScore Max (SleepScore Labs) – assessing the sleep of individuals with chronic insomnia, compared to healthy sleeper controls, in their home setting. Methods: A total of 112 individuals participated in an at-home sleep monitoring study including 83 with chronic insomnia (ages 19-65, 58 females) and 29 healthy sleeper controls (ages 19-54, 21 females). Enrollment criteria included being 18-65 years of age and, for the insomnia group, meeting International Classification of Sleep Disorders (3rd edition; ICSD-3) criteria for chronic insomnia with no other clinically relevant condition contributing to sleep disturbance. Participants used the NCD to record their sleep periods each night for 8 weeks. Sleep measurements were analyzed for group differences in both means (characterizing sleep overall) and within-subject standard deviations (characterizing night-to-night sleep variability), using mixed-effects regression controlling for systematic between-subject differences. Results: On average, individuals with chronic insomnia exhibited increased total wake time, wake after sleep onset, and decreased sleep efficiency relative to healthy sleeper controls (F>6.8, p<0.01). Additionally, they demonstrated greater night-to-night variability in time in bed, total sleep time, sleep latency, total wake time, wakefulness after sleep onset, sleep interruptions, sleep efficiency, and light and deep sleep (F>4.4, p<0.05). Conclusion: In our sample of individuals with chronic insomnia, a NCD naturalistically detected differences from healthy sleeper controls in multiple sleep parameters, both on average and in terms of night-to-night variability. Capturing night-to-night variability in the home setting adds an important dimension to our understanding of poor sleep and provides a more comprehensive, ecologically valid characterization of chronic insomnia as experienced in daily life. Support (If Any): NIH grant KL2TR002317; research devices provided by SleepScore Labs